2006
DOI: 10.1017/s0950268805005807
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of virulence factors in the newly described Salmonella enterica serotype Keurmassar emerging in Senegal (sub-Saharan Africa)

Abstract: From 2000 to 2001, nine strains of Salmonella enterica belonging to the new serotype Keurmassar have been isolated from human and poultry samples at the Senegalese National Salmonella and Shigella Reference Laboratory at the Pasteur Institute, in Dakar. All strains carried virulence factors including Salmonella Pathogenicity Islands (SPI)-1, -2, -3 and -5 encoded genes. Strains did not harbour virulence plasmid. Ribotyping analysis revealed a single clone identical to Salmonella Decatur isolated in Zimbabwe. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
(19 reference statements)
0
13
0
1
Order By: Relevance
“…Des études réalisées au Nigéria ont révélé que des souches environnementales étaient plus résistantes aux quinolones/fluoroquinolones que les souches d'origine cliniques, et cela s'expliquerait par l'utilisation intensive de ces antibiotiques en médecine vétérinaire comme facteurs de croissance et dans le traitement des infections (Chigor et al, 2010). Parfois, les résistances peuvent être d'origine chromosomique et cela par le biais d'une mutation au niveau du gène, occasionnant une modification du site de fixation de l'antibiotique, ou par efflux actif; mais le plus souvent, elles sont d'origine plasmidique, donc transférables horizontalement entre bactéries de même espèce, voire des bactéries d'espèces lointaines (Gassama et al, 2006). Bien que des souches de salmonelles hautement résistantes aux quinolones soient encore rarement isolées (Schwarz et Chaslus-Dancla, 2001), la diminution de la sensibilité doit être considérée comme une alerte, puisque les quinolones sont des antibiotiques de dernier recours contre les souches de salmonelles multi résistantes.…”
Section: Discussionunclassified
“…Des études réalisées au Nigéria ont révélé que des souches environnementales étaient plus résistantes aux quinolones/fluoroquinolones que les souches d'origine cliniques, et cela s'expliquerait par l'utilisation intensive de ces antibiotiques en médecine vétérinaire comme facteurs de croissance et dans le traitement des infections (Chigor et al, 2010). Parfois, les résistances peuvent être d'origine chromosomique et cela par le biais d'une mutation au niveau du gène, occasionnant une modification du site de fixation de l'antibiotique, ou par efflux actif; mais le plus souvent, elles sont d'origine plasmidique, donc transférables horizontalement entre bactéries de même espèce, voire des bactéries d'espèces lointaines (Gassama et al, 2006). Bien que des souches de salmonelles hautement résistantes aux quinolones soient encore rarement isolées (Schwarz et Chaslus-Dancla, 2001), la diminution de la sensibilité doit être considérée comme une alerte, puisque les quinolones sont des antibiotiques de dernier recours contre les souches de salmonelles multi résistantes.…”
Section: Discussionunclassified
“…While it is tempting to speculate that the rare occurrence of human Salmonella Cerro cases may be due to reduced virulence of this subtype, scarcity of exposure cannot be excluded as one determining cause. All tested isolates lacked spvA , a generally plasmid-mediated virulence factor found among some strains of certain, predominantly host adapted, serotypes such as Abortusovis, Dublin, or Typhimurium (Chu and Chiu, 2006; Gassama et al, 2006; Guney et al, 1994). Still, absence of this virulence gene is unlikely to explain the rare association of serotype Cerro with human cases.…”
Section: Discussionmentioning
confidence: 99%
“…and have been shown to be suitable for specific targets in different diagnostic and research laboratories [10,11]. Several studies in Africa have shown similar results [12]. In South Africa, Afema et al (2016) found similar results from treated wastewater used for the irrigation of vegetables.…”
Section: Discussionmentioning
confidence: 93%